Analysing the use trends of new psychoactive substances using wastewater-based epidemiology in Europe: A systematic review - Gabriel Gatica-Bahamonde; Elizabeth Alexandra Godynyuk; Jessica Neicun; Emmert Roberts; Mehmet Mikail Tangerli; Robin van Kessel; Katarzyna Czabanowska; Keith Humphreys; Andres Roman-Urrestarazu (Elsevier, 2023)
Background and Aims: New psychoactive substances (NPS) pose challenges not only due to their harms to users but also because they are difficult to monitor with traditional epidemiologic methods. Wastewater-based epidemiology (WBE) offers a reliable method to assess drug-taking habits in different geographical settings and their evolution over time. The aim of this systematic review was to examine NPS preferences and trends across Europe. Methods: We searched electronic databases between September 5th to 30th, 2022, included OVID/Embase, PubMed, Scopus, and Web of Knowledge. Key search terms focused on NPS, WBE, prevalence, and geographic Europe. 18 articles were included in the systematic review. All studies were WBE studies, with 17 studies collecting samples from wastewater treatment plants, one collecting from pissoirs. Due to heterogeneity across studies, a meta-analysis was not performed. Results: Literature reviewed in this study showed a trend towards stimulant-type NPS use, with the United Kingdom showing highest detection frequency. The most detected chemical class of NPS were synthetic cathinones. Southern and Western Europe showed the largest variety of NPS detected. Metabolite detection ranged extensively across countries. Conclusion: This is the first systematic review to address types of new psychoactive substances present in wastewater in Europe. Gaps in literature point to a need for standardization in wastewater-based epidemiology so that drug policies and public health policies, including drug and harm reduction services, can be targeted to those NPS that are most widely used.